The impact of the consistency of carbon performance and carbon information disclosure on enterprise value - Yan, Huahong; Li, Xiaoyan; Huang, Ying; Li, Yuanhao (Finance research letters, 2020)
•The improvement of enterprise carbon performance contributes to the improvement of enterprise value.•Active and sufficient carbon information disclosure is conducive to enhancing enterprise value.•Consistency in corporate carbon performance and carbon disclosure will have a more significant positive impact on corporate value.•Compared with state-owned enterprises, the consistency of carbon performance and carbon information disclosure has a greater positive effect on enterprise value in non-state-owned enterprises•For enterprises with a high level of corporate governance, the consistency of carbon performance and carbon information disclosure has a greater positive promotion effect on enterprise value. This study applies representative and quantifiable indicators to measure carbon performance and uses crawler technology to determine whether carbon information is disclosed in 2009-2017 manufacturing CSR reports to study the measure of the consistency of carbon performance and carbon information disclosure on enterprise value. The results show that the consistency of corporate carbon performance and carbon information disclosure has a more significant positive impact on corporate value and that this promotional effect is more obvious among non-state-owned enterprises and companies with high levels of corporate governance.